Effects of Storage-Induced Moisture Loss on Germination Performance and Oil Yield of Pongamia pinnata - Cahyono, Deddy Dwi Nur; Aminah, Aam; Putri, Atfi Indriany; Syamsuwida, Dida; Danu; Djam'an, Dharmawati; Suita, Eliya; Siregar, Nurma Wati; Nuroniah, Hani Sitti; Lukman, Abdul Haki; Bahanan, Fauzi; Utami, Eka Rachmi Budi (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Pongamia (Pongamia pinnata) is a non-food plant that has the potential to be developed as a biofuel because its seeds’ oil content is up to 40%. Therefore, it is necessary to study the characteristics of seeds for germination in relation to mass cultivation and information on oil content as a production consideration. This paper aimed to describe the sensitivity of pongamia seed moisture content to germination and its oil content and also to understand the seed category. Variations in moisture content were obtained from storing seeds at ambient temperature for up to 5 months. Moisture content, morphological characters, oil content, and germination rate were examined for each storage period. Data were analyzed using analysis of variance to determine the treatment effect. The results showed that storing seeds at ambient temperature caused a decrease in moisture content. A decrease in moisture content of 29.36% in the first month’s storage significantly affected the reduction of morphological characters and seed weight. Meanwhile, during the 2–5 months storage period, the decrease in moisture content was only 2–5% and did not affect seed length. Reducing moisture content (MC) increased oil recovery but was not statistically significant. The best germination rate was 84.67%, obtained from fresh seeds (MC of 46.64%); the germination rate decreased as the moisture content decreased during storage. Pongamia should be categorized as an intermediate seed based on the seed moisture content characteristics and germination test results. Keywords: germination, moisture content, oil content, Pongamia pinnata, storage